The slow movements: Informetric mapping of the scholarship and implications for tourism and hospitality - Klarin, Anton; Park, Eerang; Kim, Sangkyun (SAGE, 2022)
Slow food and the consequent slow movements are becoming more evident in research and media with the recognition of its implications for sustainability in many spheres of society. This study—the first systematic literature review of this topic—offers a comprehensive interdisciplinary investigation into slow movements which allows us to gain a systems view of the scholarship; stakeholder-oriented insights; and a holistic understanding of slowness while recognizing the various movements within and providing future research directions for tourism and hospitality researchers. This study identifies that slowness has extended to most aspects of our everyday life, such as the slow city, slow management, slow fashion, slow philosophy in general, and slow tourism; the latter offering COVID-19 post-pandemic recovery opportunities through sustainable tourism and hospitality. This study acts as a springboard for a better understanding of the slow(ness) movements to encourage more proactive interactions with key stakeholders and to develop the field further.